Analisis Efektifitas Pengelolaan Alokasi Dana Desa Di Desa Simbur Naik Kecamatan Muara Sabak Timur Kabupaten Tanjung Jabung Timur Tahun 2017-2021 - Indah Lestari; As’ad Isma; Nurlia Fusfita (Lembaga Pengembangan Kinerja Dosen, 2023)
This Thesis aims to determine the effectiveness of village fund allocation in simbur naik village, muara sabak timur district, tanjung jabung timur regency. One of the goals is to find out how the village fund allocation is in simbur naik village, muara sabak timur district, tanjung jabung timur regency. This study uses a qualitative approach using a quantitative approach with data collection methods by conducting observation, interview, documentation. Effective village fund allocation management in simbur naik district in 2017-2021 is in the quite effective category. The conclusions are as follows: (1) The level of effectiveness from year to year is 2017 totaled (100%), 2018 amounted to (100%), 2019 amounted to (100%), 2020 amounted to (85,19%), year 2021 amounted to (96,06). (2) The obstacles faced by the simbur naik village government, muara sabak timur district, tanjung jabung timur regency are as follows: a). Community understanding of the allocation of village funds. b). Lack of communication between work units. c). Disbursement of village fund allocations is hampered.d). Covid-19 virus. (3). Solutions reganding the obstacles faced are as follow: a). Conducting training related to the allocation of village funds. b). Improve coordination between work units. c). Make a reserve fund.